Jury Decision Making : The State of the Science - Devine, Dennis J. (Dennis John) (Book collections on Project MUSE., 2012)
While jury decision making has received considerable attention from social scientists, there have been few efforts to systematically pull together all the pieces of this research. In Jury Decision Making Dennis J. Devine examines over 50 years of research on juries and offers a ""big picture"" overview of the field. Devine summarizes existing theories of jury decision making and identifies what we have learned about jury behaviour, including the effects of specific courtroom practices, the nature of the trial, the characteristics of the participants, and the evidence itself. Making use of those foundations, Devine offers a new integrated theory of jury decision making that addresses both individual jurors and juries as a whole and discusses its ramifications for the courts.